RESPON TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) TERHADAP PEMBERIAN PUPUK ORGANIK - Allan Mamahit; Pemmy Tumewu; Marjam Toding (COCOS, 2019)
ABSTRACT This research aims to acknowledge the effect of organic fertilizing the growth and production of sweet corn which in carried out in the Village of Kauneran Satu, Sonder Sub-District during 3 months start from July – October 2018. The method of this researchment are use randomized group design with four behaviors A) None fertilizer, B) 300kg/ha of Phonska plus fertilizer, + 300 kg Urea/ha, C) 20 ton/ha organic water hyacinth fertilizer + 10 ton fertilizer from animals, D) 20 ton/ha Hydrilla Verticillata Organic fertilizer + 10 ton fertilizer from animals. The observed variable is the dried weight of the plant, the length of the cabbage, the diameter of the cabbage and the fresh weight of the sweet corn cob was measured and weighed after the sweet corn harvest. Studies have shown that treatment C 20 tons/ha organic water hyacinth fertilizer + 10 tons fertilizer from animals gives a good response to the sweet corn. Key words: Fertilizer Organic, Sweet Corn